Erosive effect of milk, honey, cereal porridge, and millet porridge on enamel of primary teeth: An in vitro study - Theresa Sam Cherian; Priya Subramaniam; Megha Gupta (Wolters Kluwer Medknow Publications, 2020)
Context: Enamel erosion is manifested as partial demineralization occurring at the enamel surface leading to increased surface roughness. Diets comprising milk, cereals, and millets are frequently fed to infants and toddlers. These foods are prepared so as to make them soft in texture, palatable, and easy to ingest. Aim: To determine the erosive effect of milk, honey, and porridges made from cereal and millet on primary tooth enamel. Settings and Design: Exfoliated caries-free primary teeth were collected, and a total of 50 longitudinal sections were prepared. They were equally divided into five groups of 10 samples each. Materials and Methods: Each group was incubated in milk, honey, cereal porridge, millet porridge, or saliva for 30 min. Subsequently the samples were washed and incubated at 37°C in saliva for 2 h. This cycle was repeated five times. The samples were gold sputter coated, and surface roughness was measured using optical profilometry. Saliva samples were evaluated for calcium release using dry chemistry method. The pH of foods and titratable acidity were also estimated. Statistical Analysis Used: One way analysis of variance and Tukey's post hoc test. Results: The mean surface roughness value, Ra (μm), obtained with millet porridge was 6.0175 ± 0.54 μm, which was significantly higher than cereal porridge, honey, and milk (P < 0.05). Calcium release in saliva was highest with honey (>14 mg/dL) and it also exhibited the lowest pH (4.33). Conclusion: Porridges prepared from millet and brown rice cereals were seen to have an erosive effect on the enamel of primary teeth.